Improving Detection Efficiency of SARS-CoV-2 Nucleic Acid Testing - Zhang, Jie; Li, Kecheng; Zheng, Ling; Zhang, Jianbo; Ren, Zhilin; Song, Tiange; Yu, Hua; Yang, Zhenglin; Wang, Li; Jiang, Li (Frontiers in Cellular and Infection Microbiology, 2020)
BACKGROUND: SARS-CoV-2 nucleic acid testing (NAT) has been routinely used for COVID-19 diagnosis during this pandemic, however, there have been concerns about its high false negative rate. We dissected its detection efficiency with a large COVID-19 cohort study. METHODS: We analyzed SARS-CoV-2 NAT positive rates of 4275 specimens from 532 COVID-19 patients in Sichuan Province with different disease severities, statuses, and stages, as well as different types and numbers of specimens. RESULTS: The total positive rate of the 4275 specimens was 37.5%. Among seven specimen types, BALF generated a 77.8% positive rate, followed by URT specimens (38.5%), sputum (39.8%), and feces/rectal swabs (34.1%). Specimens from critical cases generated a 43.4% positive rate, which was significantly higher than that of other severities. With specimens from patients at stable status, the SARS-CoV-2 positive rate was 40.6%, which was significantly higher than that of improved status (17.1%), but lower than that of aggravated status (61.5%). Notably, the positive rate of specimens from COVID-19 patients varied significantly from 85%-95% during 3 days before and after symptom onset, to 20% at around 18 days after symptom onset. In addition, the detection rate increased from 72.1% after testing one throat swab, to 93.2% after testing three consecutive respiratory specimens from each patient. CONCLUSIONS: SARS-CoV-2 NAT detection rates vary with patient disease severity and status, specimen type, number of specimens, and especially disease progression. Sampling as close to symptom onset as possible, and consecutively collecting more than one respiratory specimen could effectively improve SARS-CoV-2 NAT detection efficiency.